ADHD - New Directions in Diagnosis and Treatment 2015
DOI: 10.5772/61400
|View full text |Cite
|
Sign up to set email alerts
|

The Comorbidity of ADHD and Autism Spectrum Disorders (ASDs) in Community Preschoolers

Abstract: Symptoms of inattention and hyperactivity, features of attention-deficit/hyperactivity disorder (ADHD), have been frequently documented in children with autism spectrum disorders (ASDs) and often co-occur. Evidence indicates that 20-50% of children with ADHD meet criteria for ASD, and 30-80% of ASD children meet criteria for ADHD. According to the DSM-IV, the essential features of Autistic Disorder (AD) are "the presence of markedly abnormal or impaired development in social interaction and communication and a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 224 publications
(258 reference statements)
0
4
0
Order By: Relevance
“…Previous research has also revealed that approximately half of children with a late diagnosis of autism initially receive additional developmental diagnoses (Jónsdóttir et al, 2011), in line with our current findings. On one hand, both conditions often encompass deficits in communication and attention, as well as varying degrees of impulsivity, restlessness, or hyperactivity (Carrascosa-Romero and De La Vega, 2015). Children with a diagnosis of ADHD have shown elevated ratings of core ASD traits that could not be accounted for by ADHD symptoms or additional behavioral problems, supporting the presence of social and communication deficits in children with ADHD (Cooper et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…Previous research has also revealed that approximately half of children with a late diagnosis of autism initially receive additional developmental diagnoses (Jónsdóttir et al, 2011), in line with our current findings. On one hand, both conditions often encompass deficits in communication and attention, as well as varying degrees of impulsivity, restlessness, or hyperactivity (Carrascosa-Romero and De La Vega, 2015). Children with a diagnosis of ADHD have shown elevated ratings of core ASD traits that could not be accounted for by ADHD symptoms or additional behavioral problems, supporting the presence of social and communication deficits in children with ADHD (Cooper et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, in accordance with recent studies suggesting that social impairments are more pronounced in comorbid cases compared to individuals without this comorbidity ( 55 57 ), here only the ASD+ADHD comorbid group manifested reduced social perception both in transition and fixation variables. However, it is important to consider that until the release of the new diagnostic guidelines ( 1 ), few eye tracking studies in social cognition distinguished between these groups ( 19 , 58 ). Therefore, it is unclear if previous studies recruited participants with comorbid ASD+ADHD in their ASD groups and if the overall performance of the reported ASD group was influenced from the comorbid participants.…”
Section: Discussionmentioning
confidence: 99%
“…More children with average intelligence had ADH problems (77.20%) as opposed to low functioning (26.33%). A number of authors stress the co-occurrence of ADHD in children with ASD and place the incidence between 30% and 80% (Carrascosa-Romero & De Cabo-De La Vega, 2015). Shared heritability (Rommelse, Frankle, & Geurts, 2010) and shared endophenotypes (Holtman, Bölte, & Pousta, 2007) could explain the high co-incidence.…”
Section: Discussionmentioning
confidence: 99%